Responses of aggregates and associated soil available phosphorus, and soil organic matter in different slope aspects, to seasonal freeze–thaw cycles in Northeast China - Huang, Donghao; Zhou, Lili; Fan, Haoming; Jia, Yanfeng; Liu, Mingbo (Geoderma, 2021)
•Soil aggregate stability in shady slope was more sensitive to freeze-thaw cycles.•Well relationships exist between the aggregate fractions and available phosphorus.•Soil organic matter of partial aggregate sizes were sensitive to freeze-thaw cycles. Freeze-thaw is an important factor that affects soil aggregate size and integrity in mid-high latitudes or mountainous regions, which in turn impacts soil erosion. However, there are limited studies on the responses of aggregates and associated soil available phosphorus (AP), as well as soil organic matter (SOM) in different slope aspects to seasonal freeze–thaw cycles (FTCs). In this regard, soil samples at different depths (0–5 [D5], 5–10 [D10], 10–15 [D15], and 15–20 cm [D20]) were collected from sunny (SW) and shady (NE) slopes in Meihekou, Northeastern China. Temporal changes in aggregate size distribution, AP (extracted with 0.5 mol L−1 NaHCO3), and SOM of SW and NE were analyzed during one FTCs season (from October 2017 to March 2018). Seasonal FTCs significantly (p < 0.05) influenced aggregate size distribution and associated AP content. The results indicated that although there were similar patterns of change in soil aggregate size distribution over time between SW and NE, NE was more sensitive to seasonal FTCs than SW. The greatest reduction and increment rates were observed in aggregates sized > 5 mm and < 0.25 mm, respectively, at D5 in both SW (reduction rate = 44.9%, increment rate = 63.1%) and NE (reduction rate = 73.3%, increment rate = 76.3%). The mean weight diameters were significantly (p < 0.05) decreased by 0–22.6% in SW and 13.4–43.7% in NE at different soil depths after the seasonal FTCs. Good linear function relationships were observed between the proportion of aggregate fractions and associated AP content for aggregate sizes < 0.25 mm (r2 = 0.38**), 1–2 mm (r2 = 0.32**), and 2–5 mm (r2 = 0.42**) in SW and for > 0.25 mm (r2 = 0.68**), 0.25–1 mm (r2 = 0.38**), 1–2 mm (r2 = 0.52**), and 2–5 mm (r2 = 0.64**) in NE during the seasonal FTCs. The associated AP content showed positive correlations with the proportion of aggregates sized <0.25 mm and 0.25–1 mm and negative correlations with the proportion of aggregates sized 1–2 mm, 2–5 mm, and >5 mm in both SW and NE. The SOM was less sensitive to seasonal FTCs. After the seasonal freeze–thaw period, only the SOM content of partial aggregate sizes decreased significantly (p < 0.05) in NE, whereas there were no such significant changes in SW. Our results demonstrated that slope aspect is a key driver of the different responses of aggregates and associated AP and SOM content during the seasonal FTCs and that slope information could be useful for exploring soil erosion and nutrient loss in freeze–thaw agricultural ecosystems.